Determine the Lower-State Energy of (GaMn)As/GaAs Quantum Well using Localization Landscape Method - Mubarak H. Oglah; Sabri J. Mohammed; Moustafa S. El-Daher (Tikrit Journal of Pure Science)
The current research presented the value of the lowest state energy for (GaMn)As/GaAs Quantum Well by using the Schrodinger equation and the localization landscape method, and a comparison between the quantum confinement potential and the wavefunction localization of both the landscape method and the Schrödinger method, a great match was found between the two methods, where the Landscape method 0.1% greater than Schrodinger method. From the Hamiltonian function analysis, it was found that the quantum eigenvalues in the discrete wells interact only when the corresponding eigenvalues are close to each other. Localization appears clearly in the sub-regions of quantum well, so, we prove damping in quantum wells, especially near the boundaries of the well. The effective quantum potential W was determined.